2016
DOI: 10.1002/jbm.a.35965
|View full text |Cite
|
Sign up to set email alerts
|

Combined delivery of FGF‐2, TGF‐β1, and adipose‐derived stem cells from an engineered periosteum to a critical‐sized mouse femur defect

Abstract: Critical-sized long bone defects suffer from complications including impaired healing and non-union due to substandard healing and integration of devitalized bone allograft. Removal of the periosteum contributes to the limited healing of bone allografts. Restoring a periosteum on bone allografts may provide improved allograft healing and integration. This article reports a polysaccharide-based tissue engineered periosteum that delivers basic fibroblast growth factor (FGF-2), transforming growth factor-β1 (TGF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 91 publications
1
29
0
Order By: Relevance
“…Nevertheless, their application is still limited by the amount of available healthy periosteum . Many studies that used biotic and abiotic materials that mimic periosteum have achieved progress …”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, their application is still limited by the amount of available healthy periosteum . Many studies that used biotic and abiotic materials that mimic periosteum have achieved progress …”
Section: Introductionmentioning
confidence: 99%
“…Granero-Molto et al and Undale et al reported that transplanted MSCs enhanced callus volume, increased new bone volume, and improved biomechanical properties and could induce fracture healing by increasing biomechanical properties in mice and non-union nude rat model (52). Romero et al also described the potential of growth factor and MSCs to stimulate the healing process and new bone formation in a critical-sized mouse femur defect without inflammatory response to the graft (53). The outcome of our study is in agreement with the above-mentioned researches that declare PSC seeded in bone allograft enriched by human growth factors, which could accelerate the formation of bone callus at the fracture gap in rabbit radial CSD.…”
Section: Discussionmentioning
confidence: 99%
“…Polysaccharide based tissue engineered periosteum composed of heparin-coated chitosan nanofibers was studied in terms of delivering growth factors, support adiposederived mesenchymal stem cells (ASCs) delivery and improvement of the incorporation of the allograft in a critical-sized mouse femoral defect [144]. Female mouse received untreated allografts, allografts seeded with ASCs, allografts modified with nanofibers, or allografts modified with nanofibers and ASCs.…”
Section: Polymer Biomaterialsmentioning
confidence: 99%